Life Out of Balance : Homeostasis and Adaptation in a Darwinian World - Hagen, Joel Bartholemew (Book collections on Project MUSE., 2021)
"Focusing on the decades following World War II, Life Out of Balance examines the often fruitful attempts to apply homeostasis in a variety of biological disciplines, but also the controversies that these attempts engendered"--